The extent of happiness in the Palestinian society and its relationship to some varied variables at the beginning of the third decade of the twenty-first century: A field study applied to a sample of the population of the Palestinian community in Tubas - Alawneh, Abdelmajid Nayif (Journal of Humanities & Social Sciences, 2020)
The aim of this research is to study the issue of the extent of happiness within the Palestinian society and its relationship to some varied variables in the current time period which is the beginning of the third decade of the twenty-first century. The researcher used the descriptive analytical method and the questionnaire tool. The entire current research community represented by the population of one of the Palestinian cities in northern Palestine, as demonstrated by the characteristics of this sample, the nature of the characteristics of the Palestinian society is represented by the high percentage of males versus females and the rise of the small age group and unmarried Among those with low reproductive degrees, those with a bachelor’s degree, and those with low economic, health and family conditions, in addition to the emergence of social problems and violence in a mostly low manner, besides that the emergence of happiness was addressed within five important areas of life, and it appeared that its presence within the Palestinian society It came with a low degree, as its total value reached by (59.2%). As for the detailed areas in which happiness appeared on an average in the Palestinian society, it came to both the health field which came in at (66.4%) and the practical field which came with a value of (63.3%) ) And the behavioral field (Naf C), which came with a value of (60.7%), and these three areas are considered to be of the average degree in the presence of happiness within them as it appeared from the results of this research, in addition to other fields, namely, the societal field, which appeared with a low value (54.3%) and the political field, which appeared at a low rate as well At a value of (51.1%). As for the relationship between the variables of this research, a strong and statistically significant relationship emerged between each of the sexes, age groups, family status, number of family members, educational, economic, and health statuses and between areas of happiness within the Palestinian society that are represented in the health field, the practical field, the behavioral (psychological) domain and the field Societal and political realm. There was also a strong and statistically significant relationship between the extent of the existence of social problems and violence within the Palestinian society and the existence of happiness among the residents of this community, and at the end of the research a number of recommendations were made at the public and private levels, the most important of which was the need to work to find recreational programs by Public and private institutions in society, given that recreational behavior increases the happiness of the individual and the group together, and the need to increase faith and strengthen religious faith among individuals within families in this society, specifically in this period.